NMR investigations for a quality assessment of Italian PDO saffron (Crocus sativus L.). (April 2015) - Cagliani, Laura R.; Culeddu, Nicola; Chessa, Matilde; Consonni, Roberto
Abstract: High-resolution NMR spectroscopy was employed to analyze Italian Protected Designation of Origin (PDO) saffron from L'Aquila, S. Gimignano and Sardinia and commercial saffron samples available on the Italian market. An extensive resonance assignment of DMSO saffron extract was reported, including glucose and gentiobiose in bound and unbound form for the first time. A multivariate statistical analysis of NMR data led to a clustering of samples by performing unsupervised PCA. OPLS-DA model was successively performed to highlight the markers responsible for this discrimination. An analysis of the corresponding S-plot indicated that picrocrocin and crocins were the most relevant compounds for characterizing Italian PDO saffron. By contrast, commercial saffron barely contained these characteristic compounds, and they were primarily enriched in fatty acids. Highlights: Quality assessment of Italian PDO saffron samples by NMR metabolite analysis. Discrimination between Italian PDO and commercial saffron bought in Italian market. Identification of unbound glucose and gentiobiose anomeric signals.